2006
DOI: 10.3934/mbe.2006.3.485
|View full text |Cite
|
Sign up to set email alerts
|

An sveir model for assessing potential impact of an imperfect anti-SARS vaccine

Abstract: Abstract. The control of severe acute respiratory syndrome (SARS), a fatal contagious viral disease that spread to over 32 countries in 2003, was based on quarantine of latently infected individuals and isolation of individuals with clinical symptoms of SARS. Owing to the recent ongoing clinical trials of some candidate anti-SARS vaccines, this study aims to assess, via mathematical modelling, the potential impact of a SARS vaccine, assumed to be imperfect, in curtailing future outbreaks. A relatively simple d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(28 citation statements)
references
References 46 publications
(70 reference statements)
1
22
0
Order By: Relevance
“…Pulse vaccination is one kind of strategy characterized to be periodic in time [23, 24]. On the other hand, continuous vaccination strategy is the alternative that is descbribed by Gumel et al [25] that showed the potential impact of SARS vaccine over the pandemic that spread to over 32 countries in 2003. Alexander et al [26] built a model to study the transmission of influenza virus, computing the threshold vaccination rate necessary for community wide control.…”
Section: Introductionmentioning
confidence: 99%
“…Pulse vaccination is one kind of strategy characterized to be periodic in time [23, 24]. On the other hand, continuous vaccination strategy is the alternative that is descbribed by Gumel et al [25] that showed the potential impact of SARS vaccine over the pandemic that spread to over 32 countries in 2003. Alexander et al [26] built a model to study the transmission of influenza virus, computing the threshold vaccination rate necessary for community wide control.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications are done by considering the assumption that exposed individual can move naturally into recovered population and it is assumed that individual who has been recovered can not be re-infected by tuberculosis. Modifications of the model are also done by adding V compartment [4], namely vaccinated population, so that this model is called SVEIR model. The organization of this paper is as follows.…”
Section: Introductionmentioning
confidence: 99%
“…However, the global dynamics when the basic reproduction number is greater than one have not been resolved before. By allowing different death rates for each of the compartments, the model studied in this paper is slight generalization of the model studied in [20]. Using Lyapunov-LaSalle methods, we fully resolve the global dynamics of the model for the full parameter space.…”
Section: Introductionmentioning
confidence: 99%
“…This requires, in most cases, the use of several different techniques, such as the theory of compound matrix [25] [26], the comparison theorem [27], or the use of Lyapunov functions associated with the Lassalle invariance principle [28], to name a few techniques commonly used by authors. For example, in [20], the authors used compound matrix techniques to show the global stability of the endemic equilibrium under some constraints on the parameters of the system. Huiming Wei et al [29] proposed an SVEIR model with time delay, and analyzed the dynamic behavior under pulse vaccination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation